Current Situation and Optimization Strategy of Power Enterprise Management - Zhang, Weicheng (Journal of Theory and Practice of Engineering Science, 2023)
With the development of social economy, the scope of the use of electricity is more and more broad, and the deepening reform process of the state to the electric power enterprises is accelerated, and the electric power enterprises began to respond to the call of the state to establish a modern enterprise system. Electricity is one of the major national energy, whether electric power enterprise benign development concerns our country's energy strategy security. However, at present, the internal and external management forms are complicated, which restricts the development of power enterprise management to a certain extent. Based on this, in order for electric power enterprises to better meet the national demand, it is necessary to analyze the problems in the management of electric power enterprises at the present stage, constantly optimize and innovate the management mode of enterprises, improve the resource allocation ability of enterprises, so as to promote the development of electric power enterprises in line with The Times.